Fungsi DPR dalam Sistem Checks and Balances: Pendekatan Sosiologi Hukum Emile Durkheim - Alvin Rusdian (Universitas Proklamasi 45, 2025)
The article outlines the role of the People’s Consultative Assembly (DPR) in the Indonesian system of checks and balances using an approach based on Émile Durkheim's sociology of law. The DPR has three primary functions: legislation, budgetary affairs, and oversight. An extensive analysis of official documents such as the 1945 State Constitution of the Republic of Indonesia (UUD 1945) along with academic literature related to the roles of the DPR and theories of checks and balances demonstrates how crucially important the DPR is in safeguarding democracy and preventing abuse of power. Despite challenges like politicized budgets and a lack of transparency, appropriate reforms and increased public participation can enhance the DPR's role as a controlling agency over executive branches. Therefore, this article emphasizes the importance of maintaining the functioning of the checks and balances system in managing state finances to ensure stability and social solidarity among citizens.